CO2-Triggered microreactions in liquid marbles. Issue 66 (27th June 2018) - Luo, Xinjie; Yin, Hongyao; Li, Xian'e; Su, Xin; Feng, Yujun
Abstract : CO2 -Triggered microreactions in liquid marbles were developed by using CO2 to coalesce contacting patchy liquid marbles containing separate reagents. Abstract : On-demand initiation of dual- and multi-component microreactions inside liquid marbles (LMs) was developed by coalescing contacting patchy LMs containing separate reagents through CO2 -induced wetting transition of the interface between the LMs.